THE IMPACT OF SERVICE QUALITY AND TRUST TO CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AT BANK BCA MANADO - Tatuil, Anggreiny (Universitas Sam Ratulangi, 2013)
Customer satisfaction is the main factor that determines good or not the services company provided. It is a barometer for customers to re-use services company offered or customer loyalty using the E-banking. If the service is disappointing and customer could not believe the service company provided, will have a negative effect both for customers and the bank itself. This research is aimed to analyze the influence of service quality and trust to customer loyalty trough customer satisfaction. Theories supporting research service quality, trust, customer satisfaction and customer loyalty. This study was conducted at Bank BCA which took 100 respondents from Bank BCAâ€™s customer. in this research using random sample and path analyze method. And the conclusion are, service quality and trust positive and significant influence to customer satisfaction,service quality and trust that positive and significant to customer loyalty and customer satisfaction has positive and significant to customer loyalty. Â Keywords: service quality, trust, customer satisfaction, customer loyalty